ANALISIS TINGGI GELOMBANG AKIBAT WIND SETUP DI PANTAI SAWANGAN DENGAN METODE HINDCASTING - KRISNA KURNIARI; IDA BAGUS SURYATMAJA; MUHAMMAD AVIF RAMADHANA (GANEC SWARA, 2023)
Sawangan Beach is located directly facing the Indian Ocean, the high waves and the generation by the wind which produce great energy that hits Sawangan Beach. The coastline was a setback when, around 2010, the access from Sawangan Beach to Pura Geger had turned into rock because the sand on the beach was increasingly eroding. The increasingly steep coastal contours can interfere with fishing activities and the existence of existing groin buildings that are hit by high waves causes the position of the protective stones to not function properly. Therefore it is considered necessary to know the wave height and period at Sawangan Beach. This wave height calculation can later be used in planning appropriate coastal protection structures on the beach. Calculation of wave height in this study focuses on wave generation due to wind, which is called a wind setup using the hindcasting method. Data In determining wave height, wind data is needed. Monthly maximum average wind data from BMKG sources includes 8 directions and wind speeds. The dominant wind is cdaric eastward c, namely c40.83%. Forecasting wave height (hindcasting) from the calculation of the wind stress factor and effective fetch, the value of the wave height (H) is 2.75 meters with a wave period (T) of 10 seconds